Prolongation of Tick-Borne Encephalitis Cycles in Warmer Climatic Conditions - Zeman, Petr (International journal of environmental research and public health, 2019)
Tick-borne encephalitis exhibits profound inter-annual fluctuations in incidence. Previous studies showed that three-fifths of the variation can be explained in terms of four superimposed oscillations: a quasi-biennial, triennial, pentennial, and a decadal cycle. This study was conducted to determine how these cycles could be influenced by climate change. Epidemiological data, spanning from the 1970s to the present, and originating from six regions/countries bridging Scandinavia and the Mediterranean, represented a temporal/latitudinal gradient. Spectral analysis of time series was used to determine variation in the cycles' length/amplitude with respect to these gradients. The analysis showed that-whereas the lengths of the shorter cycles do not vary substantially-cycles in the decadal band tend to be longer southwards. When comparing the disease's oscillations before- and after the mid-1990s, a shift towards longer oscillations was detected in the pentennial-decadal band, but not in the biennial- triennial band. Simultaneously, oscillations in the latter band increased in intensity whereas the decadal oscillations weakened. In summary, the rhythm of the cycles has been altered by climate change. Lengthened cycles may be explained by prolonged survival of some animal hosts, and consequently greater inertia in herd immunity changes, slowing down a feedback loop between the herd immunity and amount of virus circulating in nature.
Keywords: klimatické změny; climate change; Climate Change; Humans; tick-borne encephalitis; time-series analysis; incidence; lidé; Encephalitis, Tick-Borne; Incidence; Animals; klíšťová encefalitida; zvířata; disease dynamics